Increase of the antitumour efficacy of the biocompound IMMUNEPOTENT CRP by enzymatic treatment - Franco Molina, Moisés Armides; Santana Krimskaya, Silvia Elena; Coronado Cerda, Erika Evangelina; Hernández Luna, Carlos Eduardo; Zárate Triviño, Diana Ginette; Zapata Benavides, Pablo; Mendoza Gamboa, Edgar; Rodríguez Salazar, María del Carmen; Tamez Guerra, Reyes Silvestre; Rodríguez Padilla, María Cristina (2018)
ABSTRACT IMMUNEPOTENT CRP is a dialyzable leukocyte extract obtained from bovine spleen with immunomodulatory and antitumour properties; therefore, when administrated as an adjuvant therapy for cancer patients, it has increased their survival and quality of life. The bioavailability of any orally administered compound can be reduced due to gastrointestinal enzymes. In this study, we evaluated if IMMUNEPOTENT CRP is resistant to the treatment with different enzymes (proteases, nucleases, polysaccharide-degrading enzymes or lipase), using as parameters for biological activity measurement its in vitro antitumour and antioxidant properties and in vivo the antitumour effect of IMMUNEPOTENT CRP treated with proteinase K. In conclusion, we consider necessary to include the antioxidant and cytotoxic activity on the MCF-7 cancer cell line as parameters for the quantitative determination of biological activity or potency tests for batch release. Additionally, the results showed that different enzymatic treatments do not affect the antitumour and antioxidant activities of IMMUNEPOTENT CRP in vitro, suggesting that this product can be administered orally without any loss of biological activity. Furthermore, IMMUNEPOTENT CRP treatment with proteinase K increases the antitumour activity in vivo.